Antiseptics for treating infected wounds: Efficacy on biofilms and effect of pH. (3rd March 2016) - Percival, Steven L.; Finnegan, Simon; Donelli, Gianfranco; Vuotto, Claudia; Rimmer, Steve; Lipsky, Benjamin A.
Abstract: Biofilm recalcitrance is a persistent problem when managing difficult to heal and infected chronic wounds. The wound biofilm is a fundamental factor in the re-occurrence and delayed healing commonly observed in non-healing and infected chronic wounds. However, there is presently no single antimicrobial agent that is completely efficacious against both the planktonic and sessile polymicrobial communities evident in at risk or infected wounds. We will review currently available antimicrobials, with particular emphasis on silver and iodine, employed to help suppress biofilms in wounds. In addition, we will also review the effect of pH on antimicrobial efficacy. Available evidence suggests that it is best to take a multifactorial approach towards controlling biofilm in chronic, "at risk" and infected wounds. This highlights the growing importance of avoiding indiscriminate or inappropriate use of antimicrobials in the treatment of chronic wounds.